Endocrine consequences of childhood obesity: a narrative review - Maroun Badr; Ghazwa El-Rabaa; Marianne Freiha; Andrzej Kędzia; Elżbieta Niechciał (Frontiers in Endocrinology)
Childhood obesity has emerged as a significant public health challenge, with profound consequences that negatively impact endocrine functions. Excess adiposity in children leads to dysregulation of various hormonal pathways, notably insulin resistance and hyperinsulinemia, the best-established endocrine changes in obesity. If insulin resistance is not adequately managed, it might precipitate type 2 diabetes. Another common finding among children with obesity is thyroid dysfunction. Some studies suggest that obesity may be associated with alterations in thyroid hormone levels, potentially leading to hypothyroidism, although the relationship is complex and not fully understood. Additionally, obesity affects the hypothalamic-pituitary-gonadal axis, resulting in precocious puberty, particularly in girls. Elevated leptin levels, a hormone produced by adipose tissue, can contribute to a paradoxical state of leptin resistance, further complicating metabolic processes and appetite regulation. Moreover, childhood obesity can result in increased secretion of cortisol, which may enhance the risk of developing metabolic syndrome and cardiovascular complications. The interplay between obesity and endocrine function also extends to growth patterns, where excess weight can lead to growth acceleration followed by potential short stature in adulthood due to early epiphyseal closure. Addressing the endocrine consequences of childhood obesity requires a comprehensive approach that includes prevention, early intervention, and management strategies tailored to this vulnerable population. Understanding these complex interactions is crucial for developing effective public health policies to mitigate the impact of obesity on endocrine health in children. By reviewing research, this work provides a comprehensive overview of the most relevant endocrine consequences of childhood obesity.